A COMPARATIVE LINGUISTICS ANALYSIS: SIMILARITIES AND DIFFERENCES BETWEEN BRITISH AND AMERICAN SLANGS - Ruminda Ruminda (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
In general, comparative linguistics deals with the comparative and contrastive examination between languages in terms of its linguistic aspects. The purpose of this research is to analyze the differences and similarities of British and American slangs based on the theory of slang classification by Allan and Burridge (2006) and its linguistic meaning concepts by Leech (1981). This comparative linguistics study utilizes qualitative descriptive methods as the research methodology through semantic theories of slang and dialect in the scope of sociolinguistics. The data is collected through random sampling of mentioned American and British slang words in a Youtube video and selected words that have the same meaning in two articles that contain the 100+ list of British and American slangs. The result of the research pointed out the more apparent similarities than differences in both dialects depicted by the Fresh and Creative, Clipping, and Imitative slang classification and the four types of linguistic meaning found in the analysis, which are conceptual meaning, connotative meaning, social meaning, and affective meaning.